PELATIHAN PEMBUATAN BOLU MARBLE PISANG KEPOK DAN PIE BROWNIES BAGI IBU PKK DI DESA PUUNDOHO - Hasria Alang; Eka Apriyanti; Hartini Hartini (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
Service activities are part of the tridharma lecturer. This activity is expected to increase knowledge and overcome problems faced by partners. Optimizing the benefits of natural resources is an important thing to do. This is intended so that these natural resources have high economic value. One of the abundant local natural resources at the service location is kepok bananas so diversification of processed kepok is deemed necessary. In addition, the observations also revealed that partners were only able to make fruit pie, which only lasted a maximum of three days, so the implementation team assumed that brownie pie making was something that could be taught to partners. The purpose of this service activity is to provide partner knowledge and skills through processing plantain marble cakes so they don't go sour and making brownie pies. The method used is training with the Asset-Based Community Development or ABCD approach by utilizing local natural resources. Partners in this activity were PKK Puundoho Village women. Changes in partner knowledge are measured through evaluation results before and after community service activities. The results of the dedication show that there has been an increase in partner knowledge and skills. In addition, activities have also provided new experiences for partners.